Molecular mechanism of LIP05 derived from Monascus purpureus YJX-8 for synthesizing fatty acid ethyl esters under aqueous phase - Zhao, Jingrong; Xu, Youqiang; Lu, Hongyun; Zhao, Dong; Zheng, Jia; Lin, Mengwei; Liang, Xin; Ding, Ze; Dong, Wenqi; Yang, Maochen; Li, Weiwei; Zhang, Chengnan; et al. (Frontiers in Microbiology, 2023)
Fatty acid ethyl esters are important flavor chemicals in strong-flavor Baijiu. Monascus purpureus YJX-8 is recognized as an important microorganism for ester synthesis in the fermentation process. Enzyme LIP05 from YJX-8 can efficiently catalyze the synthesis of fatty acid ethyl esters under aqueous phase, but the key catalytic sites affecting esterification was unclear. Protein structure modeling indicated LIP05 belonged to α/β fold hydrolase, contained a lid domain and a core catalytic pocket with conserved catalytic triad Ser150-His215-Asp202, and the oxyanion hole composed of Gly73 and Thr74. Ile30 and Leu37 of the lid domain were found to affect substrate specificity. The π-bond stacking between Tyr116 and Tyr149 played an important role in stabilizing the catalytic active center of LIP05. Tyr116 and Ile204 determined the substrate spectrum by composing the substrate-entrance channel. Residues Leu83, Ile204, Ile211 and Leu216 were involved in forming the hydrophobic substrate-binding pocket through steric hindrance and hydrophobic interaction. The catalytic mechanism for esterification in aqueous phase of LIP05 was proposed and provided a reference for clarifying the synthesis of fatty acid ethyl esters during the fermentation process of strong-flavor Baijiu.